2019
DOI: 10.1158/1940-6207.capr-18-0449
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-metabolizing Enzymes' Gene Polymorphisms and Susceptibility to Multiple Head and Neck Cancers

Abstract: Multiple primary tumors (MPT), especially in the hypopharynx and esophagus, are challenging in patients with head and neck cancer (HNC). Alcohol and alcohol-metabolizing genes were reported to be related to upper digestive tract cancers. Here, we investigated whether the genotypes of alcoholmetabolizing enzymes (ADH1B, ADH1C, and ALDH2) affected patients' susceptibility to developing MPTs. We recruited 659 male patients with HNC between March 1996 and February 2017. Age-and gender-matched controls were also re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…After the screening of titles, abstracts, and full texts, 496 articles were excluded. In total, 13 articles (14 case–control studies) comprising of 4,312 HNC patients and 6,627 controls were included in this meta‐analysis (Asakage et al, 2007; Chien et al, 2019; Hashimoto et al, 2006; Hiraki et al, 2007; Huang et al, 2017; Ji et al, 2011; Katoh et al, 1999; Koyanagi et al, 2017; Nomura et al, 2000; Yamashita et al, 2019; Yokoyama et al, 1998; Yuan et al, 2013; Zhang et al, 2014). All the included studies focused on East Asian populations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the screening of titles, abstracts, and full texts, 496 articles were excluded. In total, 13 articles (14 case–control studies) comprising of 4,312 HNC patients and 6,627 controls were included in this meta‐analysis (Asakage et al, 2007; Chien et al, 2019; Hashimoto et al, 2006; Hiraki et al, 2007; Huang et al, 2017; Ji et al, 2011; Katoh et al, 1999; Koyanagi et al, 2017; Nomura et al, 2000; Yamashita et al, 2019; Yokoyama et al, 1998; Yuan et al, 2013; Zhang et al, 2014). All the included studies focused on East Asian populations.…”
Section: Resultsmentioning
confidence: 99%
“…In 2 studies, the genotype frequencies in the control group deviated from HWE (Yuan et al, 2013; Zhang et al, 2014). With respect to genotyping, 6 studies used the polymerase chain reaction–restriction fragment length polymorphism method (Asakage et al, 2007; Katoh et al, 1999; Nomura et al, 2000; Yamashita et al, 2019; Yokoyama et al, 1998; Zhang et al, 2014), and 8 used the TaqMan method (Chien et al, 2019; Hashimoto et al, 2006; Hiraki et al, 2007; Huang et al, 2017; Ji et al, 2011; Koyanagi et al, 2017; Yuan et al, 2013). All the included information is shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One example is the study by Chien et al, in which they found that carriers of the ALDH2*2 and ADH1B*1 alcohol metabolism gene polymorphisms had higher risks of multiple primary cancers in the upper digestive tract in a Taiwanese population. 40,41 In patients with lung cancer, it has been shown that the glutathione S-transferase M1 null genotype is significantly associated for patients who had less than 40 pack years of tobacco exposure. 6 Familial aggregation of HNC was observed in this large database analysis, which was not easily investigated in usual cohorts.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Previously, we identified that alcohol metabolizing enzymes play roles in the tumor formation in upper aerodigestive tract (ADT) cancers in head and neck cancer patients [ 16 ]. In this study, we intended to search novel genetic polymorphism loci predicting the susceptibility of MPTs in OSCC patients on a genome-wide scale.…”
Section: Introductionmentioning
confidence: 99%